2018
DOI: 10.1063/1.5024243
|View full text |Cite
|
Sign up to set email alerts
|

1 mm3-sized optical neural stimulator based on CMOS integrated photovoltaic power receiver

Abstract: In this work, we present a simple complementary metal-oxide semiconductor (CMOS)-controlled photovoltaic power-transfer platform that is suitable for very small (less than or equal to 1–2 mm) electronic devices such as implantable health-care devices or distributed nodes for the Internet of Things. We designed a 1.25 mm × 1.25 mm CMOS power receiver chip that contains integrated photovoltaic cells. We characterized the CMOS-integrated power receiver and successfully demonstrated blue light-emitting diode (LED)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 26 publications
0
43
0
Order By: Relevance
“…In another work [143], a photovoltaic wireless power transfer system based on CMOS (complementary metal-oxide semiconductor) applicable for tiny (≤1-2 mm) implantable electronic devices is introduced. To integrate the photovoltaic cells, the implant contains a CMOS power receiver chip having surface area of 1.25 × 1.25 mm 2 .…”
Section: Solar-powered Wireless Systemmentioning
confidence: 99%
“…In another work [143], a photovoltaic wireless power transfer system based on CMOS (complementary metal-oxide semiconductor) applicable for tiny (≤1-2 mm) implantable electronic devices is introduced. To integrate the photovoltaic cells, the implant contains a CMOS power receiver chip having surface area of 1.25 × 1.25 mm 2 .…”
Section: Solar-powered Wireless Systemmentioning
confidence: 99%
“…After the first demonstration of a photovoltaic wireless power supply for implanted cardiac pacemaker by Murakawa et al, extensive studies have been carried out on the potential exploitation of PV cells as wireless power solutions for implantable bioelectronics, including neural devices, retinal prosthesis, etc . A modified battery‐less pacemaker (30 × 35 × 6 mm) powered by solar modules (three monocrystalline silicon solar cells connected in series) has been recently demonstrated by Haeberlin et al, as shown in Figure a.…”
Section: Energy Transfer Devices Utilize Sources From the Surroundingmentioning
confidence: 99%
“…2, the CMOS switch between the capacitor and the load is connected and the electric power is delivered from the capacitor to the target load circuit. (15) and (b) improved (18) circuits of the CMOS voltage detector circuit. At the same time, V 2 = 0 turns on M p5 and activates the additional pathway in the first-stage switch.…”
Section: Basic Design and Circuit Operation Of The Proposed Pv Power mentioning
confidence: 99%
“…At the same time, the target circuit should be sufficiently voltage-tolerant to work with the nonuniform, unstable powering pulse. We design systems with typical voltage ranges larger than 1 V (14,15,18) and the fluctuation of 0.2 V is acceptable for our applications.…”
Section: Adjustability Of Threshold Voltagesmentioning
confidence: 99%
See 1 more Smart Citation